The built environment - Hasler, Emily (Liverpool University Press, 2018)
A breath-taking collection that moves between local and distant, urban and rural, past and present. This is poetry of emotional density with a lightness of touch, structural but organic, detailed but lively, thoughtful but playful. A rare combination of exactitude and wonder leading the reader in and keeping them there.